OPTIMALISASI PERAN REMAJA DALAM PENCEGAHAN STUNTING MELALUI EDUKASI KESEHATAN DAN PENGKAJIAN STATUS GIZI - Sanggelorang, Yulianty; Sebayang, F. Ari Anggraini; Rumayar, Adisti; Masengi, Angelina Stevany Regina (Jurnal Ilmiah Tatengkorang, 2024)
Stunting, a manifestation of chronic malnutrition, affects cognitive abilities, academic performance, physical health, and economic potential. The persistence of stunting cases in North Sulawesi, particularly in North Minahasa Regency, becomes a significant issue that requires urgent attention. Health education for adolescents has been proven as an effective intervention in preventing various nutritional problems, including stunting. This Community Partnership Program (CPP) was conducted through health education and anthropometric measurements at SMP Advent Wineru and MTs Biharul Ulum, involving students from these two schools. The CPP activities comprised four stages: preparation, pre-test, health education and anthropometric measurement, and post-test. The education sessions covered basic concepts of stunting, related factors, and the role of adolescents in stunting prevention. Meanwhile, the anthropometric measurements, including weight and height, were conducted to determine nutritional status using the BMI-for-age index. A total of 57 students participated in the program. The results indicated a significant difference of students’ knowledge about stunting, before and after the health education (p-value < 0.05). The anthropometric measurements revealed that 73.7% of the students had normal nutritional status, although issues of undernutrition and overnutrition were still present. This PKM successfully enhanced adolescents' knowledge about stunting and specifically identified nutritional problems within the student population at both locations. Sustainable education and interventions are necessary to improve adolescent health and prevent stunting in the future. Stunting, manifestasi dari kekurangan gizi kronis, berdampak pada kemampuan kognitif, prestasi belajar, kesehatan fisik, dan ekonomi. Masih ditemukannya anak stunting di Sulawesi Utara, khususnya di Kabupaten Minahasa Utara, menjadi permasalahan yang perlu untuk ditanggulangi. Edukasi kesehatan pada remaja menjadi salah satu intervensi yang terbukti efektif dalam dalam pencegahan berbagai masalah gizi, termasuk stunting Program Kemitraan Masyarakat (PKM) dilakukan melalui edukasi kesehatan dan pengukuran antropometri di SMP Advent Wineru dan MTs Biharul Ulum dengan peserta siswa dari kedua sekolah ini. Kegiatan PKM terdiri dari empat tahap: persiapan, pre-test, edukasi kesehatan dan pengukuran antropometri, serta post-test. Penyuluhan meliputi konsep dasar stunting, faktor terkait, dan peran remaja dalam pencegahan stunting. Pengukuran antropometri, berat dan tinggi badan, dilakukan untuk menentukan status gizi menggunakan indeks IMT/U. Sebanyak 57 siswa berpartisipasi dalam kegiatan ini. Hasil menunjukkan terdapat perbedaan yang signifikan pengetahuan siswa tentang stunting pada saat sebelum dan setelah edukasi kesehatan (p-value < 0.05). Pengukuran antropometri menunjukkan bahwa 73.7% siswa memiliki status gizi normal, namun masih terdapat masalah gizi kurang dan lebih. PKM ini berhasil meningkatkan pengetahuan remaja tentang stunting dan mengidentifikasi secara spesifik masalah gizi pada populasi siswa di kedua lokasi kegiatan. Edukasi berkelanjutan dan intervensi diperlukan untuk meningkatkan kesehatan remaja dan mencegah stunting di masa depan